THEY AND ITS LEMMAS AS NON-BINARY THIRD PERSON SINGULAR PRONOUNS IN THE WASHINGTON POST - Tantri Refa Indhiarti; Dwi I Rizki (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2018)
In recent years, it is found that pronoun they and its lemmas are used to refer to singular person to show that the person does not wish to be identified as one of gender binaries. This phenomenon occurs in The Washington Post having added singular they to their stylebook. Therefore this paper aims at elaborating how pronouns they, them, their, theirs, and themselves are used as singular ones in the articles of The Washington Post published in 2016. With the aid of corpus instrument software, this study qualitatively analyses a small corpus consisting of 100 articles. References of pronouns identified as singular are proceeded as the data source of this study and categorized into Crystal’s (2003) main classes of noun and Cobuild’s (2011) classification of indefinite pronoun. The study reveals that The Washington Post used they as singular with the references of proper noun which consists of names of people and organizations, common count concrete noun which consists of nouns denoting persons and a noun denoting things, common count abstract noun consisting of nouns denoting abstract entities, and 6 indefinite pronouns which are used to refer to persons. These references are found mostly to be non-referential, where gender is indefinite. However, some are found to be referential which are common count concrete noun child and proper nouns in the form of names of people. These references refer to individuals who identify themselves not in one of gender binaries, instead they are found to be used in a context regarding LGBT.